2017
DOI: 10.1002/dac.3333
|View full text |Cite
|
Sign up to set email alerts
|

A secure and efficient identity‐based mutual authentication scheme with smart card using elliptic curve cryptography

Abstract: The e-commerce has got great development in the past decades and brings great convenience to people. Users can obtain all kinds of services through e-commerce platform with mobile device from anywhere and at anytime. To make it work well, e-commerce platform must be secure and provide privacy preserving. To achieve this goal, Islam et al. proposed a dynamic identity-based remote user mutual authentication scheme with smart card using Elliptic Curve Cryptography(ECC). Islam et al claimed that the security of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Amin et al 's scheme and Nikooghadam et al 's scheme, but it is pretty better than other schemes [17,19,[22][23][24]. Furthermore, we have demonstrated that the schemes of Amin et al and Nikooghadam et al suffer from various vulnerabilities.…”
Section: Security and Performance Comparisonmentioning
confidence: 64%
See 2 more Smart Citations
“…Amin et al 's scheme and Nikooghadam et al 's scheme, but it is pretty better than other schemes [17,19,[22][23][24]. Furthermore, we have demonstrated that the schemes of Amin et al and Nikooghadam et al suffer from various vulnerabilities.…”
Section: Security and Performance Comparisonmentioning
confidence: 64%
“…We compare the proposed scheme with other recently introduced schemes [15,17,19,20,[22][23][24] in this section. Table 3 shows the results of security analysis.…”
Section: Security and Performance Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al's scheme 39 are powerless against man‐in‐the‐middle attack and user/server impersonation attack, and fails to provide perfect forward secrecy and user anonymity. Maitra et al's scheme, 45 Luo et al's scheme, 46 and Amin et al's scheme 40 are powerless against password guessing attack and user/server impersonation attack.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…This section compares the new protocol with other related protocols (ie, References 39,40,[44][45][46] in terms of security and performance.…”
Section: Performance Evaluationmentioning
confidence: 99%